Annual review of comparative and international education 2015 - Wiseman, Alexander W., 1968-; Anderson, Emily (Bingley, U.K. : Emerald, 2016)
The goal of the ARCIE volume is to examine current perspectives and future directions for the field using several essays as a context for discussion and analysis. The format of ARCIE pieces entails an analytic overview of published work in the field, noting key issues and future directions. It provides an important and well-cited international forum for the discussion of matters of comparative and international education theory, policy and practice.
Building a foundation for reflecting on comparative and international education : a synthesis of published comparative education research / Alexander W. Wiseman ... [et al.] -- Mapping the purposes of comparative and international education research : a comparative study of four leading journals / Stephanie A. Sell -- Reflecting on gender and education research and practice in the field of comparative and international education : past, present, and future / Caroline Manion -- Understanding the internationalization of education and its demand for a business of knowledge : emerging issues and discussions in Canadian comparative and international education / Lynette Shultz -- Facilitating CIE's journey up into the educational trenches : a discussion essay / Karen L. Biraimah -- Comparative education in Egypt : trends, directions, and aspirations / Ahmed Ismail Heggi -- Metaphorical trajectories of comparative and international education research in the Asia-Pacific / Brian D. Denman -- Czech comparative education : revitalization, issues, and trends / Elis<U+030c>ka Walterova<U+0301> -- Comparative education in an age of crisis : challenges and opportunities in contemporary Italy / Anselmo R. Paolone -- Comparative and international education in Germany : a discussion of current trends / Marcelo Parreira do Amaral, Hans-Georg Kotthoff -- Reframing the center : new directions in the qualitative methodology in international comparative education / Supriya Baily, Payal Shah, Meagan Call-Cummings -- Doing mixed methods research in comparative education : some reflections on the fit and a survey of the literature / Qiang Zha, Derreck Tu -- Education for youth at the borderlands : developing comparative and international education between states / Allyson Krupar, Esther Prins -- Measuring learning outcomes in Kenya : context and perspectives / Laban P. Ayiro -- Two worlds apart in Botswana's education system : lessons for the 2010 examinations crisis / Agreement Lathi Jotia, Keene Boikhutso -- STEM learning achievement among Cambodian middle school students : an examination of gender and psychosocial factors / Sothy Eng, Whitney Szmodis -- National-postnational-transnational? Changing conceptualizations of citizenship in comparative and international education research / Dobrochna Hildebrandt-Wypych.
Includes index.
Print version record
Keywords: Education -- Comparative; Education; Comparative education; International education